Utilização de dry heat treatment em amido de ervilha: investigação das propriedades térmicas, estruturais, morfológicas, de pasta e digestibilidade in vitro - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Pea is one of the pulses cultivars most widely defunded around the world, and it represents a cheap starch source compared to cereals and tubers.Pea starch is a byproduct of protein extraction and presents a high resistant starch content. However, pea starch in its native form has limited technological applications because of characteristics such as its tendency to retrograde. The DHT, Dry Heat Treatment, is a physical modification of low cost, low risk, and non-residue technique. It can alter the physical-chemical properties and digestibility of starches.In the present study, DHT was applied to pea starch with nine treatments, using three temperatures and three treatment times to evaluate the alteration caused in pasting, thermal, structural properties, and digestibility of pea starch. The treatments at 150 °C significantly decreased the starch viscosity, from 1039,5 mPa.s-1 to 327,5, 247,5 e 33,5 for thr 2, 4 e 6 h treatments, respectively.Also, enhanced the transition temperatures, and decreased the gelatinization enthalpies of some samples, although there was no significant alteration in starch structure. These results point to modifications that occurred in the amorphous regions, suggesting lower swelling degree and lower amylose leaching, which makes the starch suitable for applications in pasta production. The modified starches were also more stable to applied shear force and heat and showed a decreased tendency towards retrogradation. The native starch showed a great resistant starch content (71,55%). The DHT treatment enhanced this contente to 86,54 and 86,33%, for the samples with greatest increase, DHT 150-4 and 130-2, respectively. These results enhance the application of modified pea starch in functional foods possibilities.
Keywords: Modificação física; Amido modificado; Calor e baixa umidade; Fonte alternativa; Amidos não-convencionais; Physical treatment; Modified starch; Heat and low moisture; Alternative source; Non-convencional starch; CNPQ::CIENCIAS AGRARIAS